Efficacy of customized soft occlusal splints in the management of temporomandibular joint disorders among the population of Parsa District of Nepal: A cross-sectional study - Sartaj Singh Wazir; Alok Kumar Jaiswal; Rahul Srivastava (Wolters Kluwer Medknow Publications, 2022)
Background: In recent years, temporomandibular joint disorders (TMDs) have been a highly debated topic. TMD is the collective term of clinical problems that involves the masticatory apparatus, temporomandibular joint (TMJ), and its associated structures or both. It is really a tough challenge for both the dental and the medical specialists and is often difficult to diagnose and treat such a disorder as the presenting symptoms can be variable. A variety of treatment modalities have been described in the literature for its management and the conservative method is most preferred. The objective of the present study was to evaluate the effectiveness of soft occlusal splint therapy among the population of Parsa district of Nepal in the management of TMDs. Materials and Methods: Thirty subjects with signs and symptoms of TMDs were included in the study, out of which 13 (43.3%) subjects were males and 17 (56.7%) were females, with age ranging from 21 to 40 years. Soft occlusal splints were given to the patients for about 3 months and evaluated for reduced mouth opening, tenderness of TMJ (preauricular), TMJ sounds, and mandibular deviation after 1 week of initiation of therapy and every month for 3 consecutive months. Results: There was a significant improvement of 3.06 mm (9.7%) in mouth opening, 86.7% of subjects showed significant reduction in preauricular tenderness, 80.0% subjects showed reduction in TMJ sounds, and 76.7% of subjects showed improvement in mandibular deviation after 3 months of the splint therapy. Paired t-test and Chi-square tests were done for comparison. Conclusions: Soft occlusal splints can be used effectively as a conservative treatment modality in reducing the signs and symptoms related to TMDs.